Indonesian Gen Z in Travel Information Search: A Qualitative Study Using the Uses and Gratifications Theory - Ni Putu Dhanan Kumaradewi M; I Gusti Ayu Agung Istri Dinda Larasshanti Jelantik (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study provides exploratory insight into how Generation Z users search for travel information on TikTok, interpreted through the lens of the Uses and Gratifications Theory (UGT). Using a qualitative phenomenological design, data were gathered through in-depth interviews with five female respondents aged 20–29 from major Indonesian cities. Thematic analysis with NVivo 15 identified four interconnected gratification dimensions: affective gratification, social gratification, cognitive-credibility gratification, and cognitive-efficiency gratification. These findings reveal that TikTok functions not merely as an entertainment platform but as an algorithmically mediated information ecosystem that blends emotion, trust, and efficiency in digital discovery. From a theoretical perspective, the study contributes to the contextual application of UGT by introducing the exploratory concept of Algorithmically Mediated Gratification (AMG). Practically, the findings offer actionable insights for business owners and tourism marketers by designing authentic, visually compelling, and interactive short-form content, collaborating with credible micro-influencers, and maintaining consistency across digital platforms to enhance user trust and engagement.